The impact of media coverage on history: The rise and fall of Richard Nixon - Csorba, Eszter Zsuzsanna (AMERICANA E-journal of American Studies in Hungary, 2018)
Richard Nixon was famous for many things on a political level; however, he was also prominent figure when it comes to the history of media. The research focuses on those encounters between the media and Richard Nixon that yielded unprecedented milestones in media history. For the paper, recordings, video tapes, transcripts and photographs were analyzed to showcase the significant changes that have occurred since. The list of game-changing events that Nixon was involved in is very long and sometimes overlooked because books dealing with the history of media rarely go into detail. For that reason the impact of the media was chosen to be observed in this paper through the political career of a president within the political history of the United States.